Edukasi dan Pelatihan Menjaga Kesehatan Reproduksi Remaja Putri dengan Ramuan Tradisional - Hadi Barru Hakam Fajar Siddiq (Warta Pengabdian, 2018)
Community service activities undertaken by lecturers from Pharmacy Diploma III Program of Pharmacy Academy of Jember held on February 5, 2017, held at MTs. and MA. Habiburrahman Jatian, Pakusari Jember provides benefits for students in terms of maintaining reproductive health. MTs. and MA. Habiburrahman is junior high school and senior high school under the Ministry of Religious Affairs located in Jatian-Pakusari-Jember. MTs. and MA. Habibirrahman also has a religious education institution that is Pondok Pesantren Habibirrahman. Nearly 90% of students and female students of MTs. and MA. Habiburrahman is santri. The results show that the knowledge of female students of MTs and MA Habiburrahman on how to maintain reproductive health are in very good category. However, in terms of student behavior against the usage of soap cleaning or betel soap to clean the feminine area showed poor results. As many as 22 students of MA and 24 female students of MTs or about 84% of female students of MA and 46% of MTs students never cleaned the feminine area with cleansing soap or betel soap. the behavior of female students in making traditional herbs to maintain reproductive health showed poor results. More than 70% of MTs and 96% of female students of MA Habiburrahman never made traditional herbs to maintain female reproductive health.